In Defense of John Rawls's Solution to the Problem of Incompatible Pluralism in Democratic Society and an Application of Political Liberalism in Our Own - Lapin, John Jacob. (Tufts Archival Research Center, 2005)
Most political philosophies have tried to argue in favor of a particular idea of the good and have tried to convince others to endorse that idea. But can we really hope to enact public policy based on a single idea of the good in a democracy, where there is a pluralism of reasonable views? In this thesis, I argue that the only way we can hope to create legitimate and stable public policy is by setting aside the points of contention, since we will never agree on those anyway, and since enacting policy for everyone based exclusively on a particular view would be unduly coercive to those who do not hold that view. I will argue that we have a duty to our fellow citizens to deliberate publicly by presenting each other justifications for views that we reasonably think other citizens like us would accept. In the first half of my thesis, I will explore and defend John Rawls's expression of this view. Though I will use the contemporary abortion debate as an example of a contentious culture war issue that could be resolved through a Rawlsian framework, the solution could be used for other issues, too. In the second half of my thesis, I will broaden his view to apply it to our actual polity to show how we can make 21st century American democracy more legitimate, stable, and transparent.